Systematic Review and Meta-Analysis of Surgical Zipper Technique versus Intracutaneous Sutures for the Closing of Surgical Incision. - Dezhi Chen; Jian Song; Yong Zhao; Xun Zheng; Aixi Yu (PLoS ONE)
Background It is controversial whether surgical zipper technique (SZT), a non-invasive method of surgical wound closure, achieves a better outcome of incision healing than intracutaneous sutures (IS) in the surgery. This meta-analysis was performed to systematically analyze whether surgical zipper is superior to suture material for the incision closure. Methods Databases and reference lists were searched for randomized controlled trials (RCTs) comparing SZT with IS for the incision closure. Results Four RCTs with 678 patients were identified and analyzed. Compared with IS, SZT achieved similar incidence of postoperative complications, less time for incision closure, less cost of both surgeons' time and operating room time, no need for removing sutures and more comfort for the patients. Besides, SZT achieved perfect aesthetic results in various types of incisions with the exception of those with substantial curvatures, those with secretions, in obese patients or those under high tension. Conclusion The non-invasive zipper technique may be a more attractive option of incision closure in a wide spectrum of surgical areas.